SOSIALISASI PENCEGAHAN KEKERASAN SEKSUAL TERHADAP ANAK DI SMP NEGERI 3 LIMBOTO - Mozin, Nopiana; Kamuli, Sukarman; Ngiu, Zulaecha; Al Hamid, Saleh; Nggilu, Ariyanto; Rusli, Puput Riana (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
A child is one of the creatures entrusted by God to be cared for, guided and given affection. One of the rights of children is to get an education, and teaching both at home, school and in the community. The child also has the right to have legal protection of his / her self both physically and mentally. Children who are vulnerable to physical or sexual violence are also entitled to legal protection. Gorontalo, especially the number of sexual violence against children, is increasing, this is clearly one of the problems faced by the government. Therefore, collaborative community service conducted by lecturers and students by involving education units in SMP Negeri 3 Limboto is considered very important. The implementation method is packaged in the form of pengbadian socialization prevention of sexual violence in SMP Negeri 3 Limboto Anak. Its purpose is to provide understanding and education on how important it is to protect children's rights and prevent children from the dangers of sexual violence.